2020
DOI: 10.1002/cncr.33213
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic and molecular analysis of early‐onset gastric cancer

Abstract: BACKGROUND: Evidence suggests that early-onset gastric cancers are distinct from traditional gastric cancers; however, detailed genomic and morphologic characterization of these cancers has not been performed. METHODS: Genomic analysis was performed for 81 patients with gastric cancer who were 50 years old or younger; pathology slides were available for 53 of these patients, and they were re-reviewed to perform a morphologic-molecular correlation analysis. The results were compared with corresponding cBioPorta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Globally, there have been several reports of increasing incidence of early- or young-onset cancers [ 1 ]. These encompass a spectrum of solid organ cancers such as colorectal cancer (CRC) and adenocarcinomas of the pancreas [ 2 ], breast [ 3 ], ovary [ 4 ], oesophagus [ 5 ], and stomach [ 6 ]. Though CRC has demonstrated the most striking trend, similar patterns have been uncovered in other gastrointestinal adenocarcinomas.…”
Section: Introductionmentioning
confidence: 99%
“…Globally, there have been several reports of increasing incidence of early- or young-onset cancers [ 1 ]. These encompass a spectrum of solid organ cancers such as colorectal cancer (CRC) and adenocarcinomas of the pancreas [ 2 ], breast [ 3 ], ovary [ 4 ], oesophagus [ 5 ], and stomach [ 6 ]. Though CRC has demonstrated the most striking trend, similar patterns have been uncovered in other gastrointestinal adenocarcinomas.…”
Section: Introductionmentioning
confidence: 99%
“…The term young-, or early- onset cancers ( 1 , 2 ) encompasses a spectrum of solid organ cancers occurring in individuals under the age of 40 years [although some authors extend the upper limit of the age-group to include those <50 years ( 3 )] in whom the aetiology of their cancers cannot be traced back to pre-existing familial cancer syndromes ( 4 6 ). This entity has been reported to affect nearly every solid organ including the pancreas ( 7 ), breast ( 8 ), ovarian ( 5 ), oesophageal ( 9 ), colorectal ( 10 , 11 ), and gastric ( 12 ) cancer, amongst others. The large number of reports on the rising incidence of this entity from around the world ( 3 , 13 15 ) have left oncologists questioning the cause for the cancers and their disturbing trend.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have found that there are also CDH1 germline mutations in EOGC (30,31). Integrative genomic analysis found that higher proportions of early-onset diffuse gastric cancers (DGCs) contain somatic mutations in CDH1 which were associated with shorter survival times compared with late-onset DGCs (32)(33)(34). Interestingly, no clear CDH1 variants were found in Brazilian EOGC patients, and eating habits may be related to the development of EOGC (35).…”
Section: Discussionmentioning
confidence: 99%